2012
DOI: 10.4187/respcare.01082
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Slow Expiration With Glottis Opened in Lateral Posture (ELTGOL) on Mucus Clearance in Stable Patients With Chronic Bronchitis

Abstract: BACKGROUND: Slow expiration with glottis opened in lateral posture (ELTGOL, l'expiration lente totale glotte ouverte en infralatéral) has been used in clinical practice to improve mucus clearance from peripheral airways. The purpose of this crossover study was to evaluate the effect of ELTGOL on mucus clearance of right and left lungs, especially of peripheral lung areas, in stable patients with chronic bronchitis. METHODS: Twelve 45-75-year-old patients with chronic bronchitis were studied (10 of whom had mil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 28 publications
2
33
0
Order By: Relevance
“…Slow expiration with the glottis opened in the lateral posture (ELTGOL) [12] is an ACT whose effect is based on increasing airflow resistance and air flow-mucus interaction [13] by reducing the diameter of the peripheral airways of the inferolateral lung. This reduction in diameter results from the weight of the superolateral lung and mediastine, from inferolateral hemidiaphragm displacement in a cephalad direction due to compression of the viscera, and from slow and prolonged expiration, which confers the added benefit of avoiding airway collapse [12,13]. On studying the ELTGOL efficacy in a single session in 15 patients with CF and 10 patients with bronchiectasis, it was found that secretion removal was greater than that obtained with Flutter [7,14].…”
Section: Introductionmentioning
confidence: 99%
“…Slow expiration with the glottis opened in the lateral posture (ELTGOL) [12] is an ACT whose effect is based on increasing airflow resistance and air flow-mucus interaction [13] by reducing the diameter of the peripheral airways of the inferolateral lung. This reduction in diameter results from the weight of the superolateral lung and mediastine, from inferolateral hemidiaphragm displacement in a cephalad direction due to compression of the viscera, and from slow and prolonged expiration, which confers the added benefit of avoiding airway collapse [12,13]. On studying the ELTGOL efficacy in a single session in 15 patients with CF and 10 patients with bronchiectasis, it was found that secretion removal was greater than that obtained with Flutter [7,14].…”
Section: Introductionmentioning
confidence: 99%
“…[24][25][26] However, it should be remembered that mucociliary clearance is predominant in the dependent lung areas of semi-sitting infants, as in adults, being stimulated by regional ventilation. [27][28][29] No wonder that conventional CPT gives poor results and is poorly tolerated, with side effects such as esophageal reflux, tachypnea, tachycardia, hypoxemia, rib fracture, and severe central nervous system complications, especially in newborns. [30][31][32][33][34] The 2012 Cochrane review showed no significant benefit from conventional CPT on clinical score or hospital stay, and conventional CPT in acute viral bronchiolitis is no longer recommended.…”
Section: Chest Physical Therapymentioning
confidence: 99%
“…2,3,5 The technique is based on the expiratory phase, which has to be prolonged and slow. Although ELTGOL has been used since the 1990s, to our knowledge, this is the first description of the amount of ERV exhaled using this technique.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have studied ELTGOL in subjects with chronic lung diseases. [3][4][5][6][7] Martins et al 3 reported an increase in mucus clearance in the peripheral area in subjects with COPD after ELTGOL by radio aerosol inhalation, even though Kodric et al 7 observed limited benefits (no difference at hospital discharge) in subjects with COPD with exacerbations compared to a control group.…”
Section: Introductionmentioning
confidence: 99%